PENGARUH BRAND EQUITY, BRAND IMAGE DAN SUASANA TOKO (STORE ARMOSPHERE) TERHADAP MINAT BELI PADA TOKO H&M DI TUNJUNGAN PLAZA SURABAYA - Jaya, Aulia Ramadhani; Maruta, IGN Anom; Pratiwi, Ni Made Ida (Universitas 17 Agustus 1945 Surabaya, 2020)
Surabaya City is currently popping up a lot of new retailers ranging from local brands to foreign brands, from brands with low prices to brands with high prices even with quality that is not much different. At present many foreign brands have entered Indonesia, including Surabaya. An example is the H&M store, not even a few fans of this brand. it doesn't even feel like the local brands have begun to be removed from the market. The purpose of this study is to determine the effect of Brand Equity, Brand Image, and Store Atmosphere that can influence consumer buying interest in products that cannot be said to be cheap goods.This type of research is the type of research is quantitative research. The study population is consumers who have bought, visited, and used products at the H&M store in Tunjungan Plaza Surabaya. While the sample is 100 respondents. Data processing techniques in this study use the Statistics Program for Social Science (SPSS). The results of this study indicate that, Brand Equity, Brand Image, and Store Atmosphere have a strong influence jointly on buying interest in H&M stores in Tunjungan Plaza Surabaya. Based on the conclusions, it is hoped that H&M Stores will further improve the quality of existing products and develop innovative products that are currently owned so that it can influence consumer buying interest. Keywords : Brand Equity, Brand Image, Store Atmosphere, Purchase Interest.